2016
DOI: 10.1111/ibi.12390
|View full text |Cite
|
Sign up to set email alerts
|

The role of nest‐site selection and cereal production in differential nest predation in Common Quail Coturnix coturnix and hybrid quail C. coturnix × C. japonica

Abstract: In Europe, farm‐reared quail used for restocking purposes are often hybrids between the Common Quail Coturnix coturnix and the Japanese Quail Coturnix japonica. These hybrids interbreed with wild Common Quail populations and suffer higher rates of nest predation, which would suggest that the two quail types have different nest‐site selection patterns. We monitored 103 radiotagged nesting females (77 wild Common Quail over 18 breeding seasons and 26 hybrid quail over six breeding seasons) and analysed their nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
(77 reference statements)
0
7
0
3
Order By: Relevance
“…This difficulty to infer admixed genotypes to a predefined hybrid class can originate from either a weak genetic resolution of our microsatellite marker panel or a low frequency of hybrids in populations. A low frequency may result from the combination of a low survival of partridges released on the field (< 30% a few months after release, Bro et al 2016), a lower reproductive success of the released partridges (Buner et al 2011)-that could be due to a less effective antipredator behaviour (see Mayot et al 2012) as also observed in the quail (Capdevila et al 2016)-or from the rapid disappearance of the hybrid genetic signature as first back-crosses occur.…”
Section: Differences Between Wild and Farmed Partridgesmentioning
confidence: 99%
“…This difficulty to infer admixed genotypes to a predefined hybrid class can originate from either a weak genetic resolution of our microsatellite marker panel or a low frequency of hybrids in populations. A low frequency may result from the combination of a low survival of partridges released on the field (< 30% a few months after release, Bro et al 2016), a lower reproductive success of the released partridges (Buner et al 2011)-that could be due to a less effective antipredator behaviour (see Mayot et al 2012) as also observed in the quail (Capdevila et al 2016)-or from the rapid disappearance of the hybrid genetic signature as first back-crosses occur.…”
Section: Differences Between Wild and Farmed Partridgesmentioning
confidence: 99%
“…Although a number of studies have emphasized the higher probability of predation risk in field margins (e.g. Paton 1994, Batáry & Báldi 2004, Capdevila et al (2016) found no edge effect in Common Quail nest predation probability. Apart from grassy strips, previous studies in Europe emphasized the role of woody ecotones (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, we found only slight effect of field margins. Capdevila et al (2016) found that female quails preferred to nest near field margins, which might be related to the greater food resources and more suitable nest cover. Although a number of studies have emphasized the higher probability of predation risk in field margins (e.g.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Synthetic reviews suggested that high nest survival rate may be attributed to the extended breeding season (Jansen and Crowe 2005) and available supplemental food sources (Sandoval and Barrantes 2012). Meanwhile, the predation (Ellis-Felege et al 2013; Carpio et al 2014;Capdevila et al 2016;Lyly et al 2016), competition (Robel et al 2003;Hämäläinen et al 2012), extreme weather condition (Kobayashi and Nakamura 2013) and temperature effects (Xu et al 2008) were likely to be the principal causes of nest failure.…”
Section: Macroscopic Ecologymentioning
confidence: 99%